Effect of Supervised Physiotherapy in Ankylosing Spondylitis - Taslimuddin, Md; Moyeenuzzaman, Md; Islam, Md Quamrul; Hasan, Suzon Al; Rahman, Md Habibur (TAJ: Journal of Teachers Association, 2011)
DOI: http://dx.doi.org/10.3329/taj.v15i1.8381 TAJ 2002; 15(1): 37-42